Preparation, Optimization and Physicochemical Characterization of a Biodegradable Core-Shell Chitosan/Alginate Hydrogel Composite - Misson, Mailin; Max Michael Samson; Yong , Wilson Thau Lym; Suryani Saallah; Hesham El Enshasy (Journal of Tropical Life Science, 2026)
Excessive and inefficient fertilizer use in agriculture poses significant environmental and economic concerns, creating a demand for sustainable alternatives. Natural polymer-based hydrogels, particularly those derived from biopolymers such as chitosan and alginate, offer promising potential due to their biodegradability, biocompatibility, and water-retaining properties. However, limited studies have systematically optimized core–shell hydrogel systems based on natural polymers for their potential as nutrient carriers particularly in agricultural applications. The present study focuses on the preparation, statistical optimization and characterization of a core–shell chitosan/alginate (Chi/Alg) hydrogel system using CaCl₂ as a crosslinker. Key formulation parameters including polymer and crosslinker concentrations were optimized to enhance swelling capacity, water retention, and hydrogel yield. Results showed that higher chitosan concentrations led to significantly greater swelling (up to 1652%), while increased crosslinker concentrations accelerated water loss. Water retention improved at lower alginate–CaCl₂ concentrations, and hydrogel yield increased with higher alginate–chitosan ratios. Core–shell thickness varied with solidification time (1–40 minutes), ranging from 404.11 ± 18.47 µm to 735.33 ± 24.31 µm. Physicochemical characterization confirmed the materials’ structural composition and suitability as a nutrient carrier. SEM-EDX revealed particle sizes of 38–225 µm with porous, fibrous morphologies in hydrated form and successful Ca²⁺ crosslinking. FTIR spectra showed ionic interactions and characteristic shifts in amide groups. This study presents a novel, biodegradable core–shell hydrogel system optimized for nutrient carrier potential, contributing to the advancement of eco-friendly materials in sustainable agriculture.